Aberrant Drainage of the Umbilical Vein Into the Coronary Sinus Without Ductus Venosus Agenesis. (1st March 2014) - Brahim, Foued Ben; Hazelzet, Tristan; Cohen, Laurence; Durand, Isabelle; Blanc, Julie; Barre, Elise; Daudruy, Marie Brasseur; David, Nadine
Abstract : We describe a case series of 4 fetuses with ectopic connections of the ductus venosus to the coronary sinus detected prospectively between August 2011 and February 2012 in 2 congenital cardiologic centers. An enlarged coronary sinus alerted the sonographer. Fetal echocardiography showed ectopic connection of the ductus venosus in an enlarged coronary sinus in all 4 cases. To our knowledge, this anatomic form of ectopic umbilical vein drainage has not previously been reported. The infants were doing well. This venous variant should be considered in cases of isolated coronary sinus dilatation after elimination of a left superior vena cava and a totally anomalous pulmonary vein connection.